Hydro-morphological characteristics in relation to soil conservation planning of Hathamati watershed - HIRAPARA, PARAS; GAUR, M.L.; PATEL, G.R.; TIWARI, M.K.; TRIVEDI, M.M. (Journal of Soil and Water Conservation, 2023)
Hathamati river basin is physiologically and hydrologically important for the Sabarmati River basin. Morphometric analysis and drainage network analysis was carried out for the Hathamati watershed to understand its drainage characteristics and the drainage patterns geometry which directly affect the watershed area. This study has attempted to justify hydro geomorphology of the Hathamati watershed via basin morphometry analysis for proper implementation of land and water management practices. SRTM DEM (provide 30 m spatial terrain resolution), geological and hydrological maps of the Hathamati area and it has been done with help of ArcGIS 10.3 environment of this analysis. The study is mainly focused on Hathamati watershed in from first to sixth orders drainage network. Results shows that a 1288.86 km total stream length of all orders was found distributed within 1305.09 km2 drainage area in a dendritic pattern. Analysis prove that the drainage density and form factor have highly correlated each other compare to drainage texture. In general, the study asserted that the watershed was underlain by uniform resistance rock, less erosion prone in lower area, and susceptible to soil erosion in upper area of Hathamati watershed. Morphometric analysis could useful for enhance/ strengthen water utilization and storage capacity, sediment loss from watershed that rehabilitate its productivity.